HUBUNGAN ANTARA PENGETAHUAN KEWIRAUSAHAAN DAN MINAT BERWIRAUSAHA PADA SISWA KELAS XI TEKNIK PEMESINAN SMK SEMEN PADANG - Muhammad Abdul Affan; Febri Prasetya; Ambiyar Ambiyar; Andril Arafat (Jurnal Vokasi Mekanika (VoMek), 2024)
The purpose of this study is to determine the extent to which class XI Machining Engineering students at SMK Semen Padang have an interest in entrepreneurship and entrepreneurial expertise. It is thought that having an understanding of entrepreneurship might have a significant role in influencing students' decisions to pursue careers in business after graduation. A quantitative approach using a survey methodology is the research method employed. The study's demographic and sample comprised 51 Mechanical Engineering class XI students. Information was gathered using surveys and objective assessments that gauged students' interest in and degree of entrepreneurial expertise. The findings demonstrated a strong and positive correlation between students' interest in entrepreneurship and their knowledge about it. The product moment correlation test is a component of hypothesis testing. The calculated sig value (2-tailed) 0.002 <0.005 with a significance level of 5% and falls into the medium group, according to the data analysis calculations. Therefore, it can be said that, in the 2023–2024 academic year, SMK Semen Padang's class XI machining engineering students' entrepreneurial knowledge and interest are positively correlated.